PRODUCTION AND CHARACTERIZATION OF IMMUNOGLOBULINE YOLK AS ANTI ANTIGEN MEMBRANE TOXOPLASMA GONDII - Puspitasari, Heni; Praptiwi, Yuliana; Suwanti, Lucia (Indonesian Journal of Tropical and Infectious Disease, 2016)
Toxoplasma gondii is an obligate parasite intracellular which can infected human and other mammalian. Immunoglobulin Y technology  offers several advantages better than antibody production in mammals. This research was aimed to get immunoglobulin Y from egg yolk, to prove that antibody against membrane T. gondii antigen can produced from immunoglobulin Y and to know the characterization of  immunoglobuline Y according to  molecular weight by SDS PAGE and reactivation of  antibody antigen  by Western Blott. This research devided  from many step : passase tachyzoites T. gondii into mice by peritoneal infection, cultivated  the tachyzoite from intraperitoneal fluid, preparation of  membrane antigen tachyzoite T. gondii, then  immunization laying hens with membrane antigen, extraction and purification immunoglobuline Y from egg yolk and then protein analyzed by SDS PAGE and Western Blott.  The result of this resarch showed that immunoglobulin Y from egg yolk can  produced antibody against protein membrane T. gondii. The result of analyzed profile protein immunoglobuline  Y according SDS PAGE  has molecular weight 179,8 kDa. Analyzed from Western Blott showed that immunoglobulin Y can recognize antigen epitope of  T. gondii on molecular weight 35,7 kDa and 78,8 kDa.